(3GfOeGL GdHfhc hehGLgI BKGQ GdYhdeI (B/s - (3ehSi, eMeO GHQGgje s ((3GdGScfOQjI (B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2004)
(3jVe GdEWGQ GdbGfhfj ddEfOeGL, GdEfOeGL GdeUQaj VQhQI YUQjI(B.s
(3HjHdjhZQGajG(B: (3U U(B.179-196s
Keywords: (3GdHfhcs